O não-todo significante do feminino em Lacan - Braga, Leticia Ferreira (2023)
The present work aimed to investigate how the feminine position happens in relation to the significant Other (A), the phallic significant, in Lacan. For that, a cut of the Lacanian route was chosen, in which the focus is that the female position has the characteristic of being not-whole in front of the phallic meaning. A research consenting to the bias that the sexual position is not limited to genders, to body anatomies, on the contrary, it is about signifiers. Thus, initially this research revisits the freudian theory of the Oedipus Complex, through which the enigma of the feminine will be put into perspective, in a dialogue with authors who agree that the feminine position is related to the signifier of the phallic function, but that something escapes the significance that the Other has. Then, this work puts in view that the incompleteness that fundamentally characterizes the place of the Other (A) is announced in a lacanian way by understanding the signifier of the barred Other, S(Ⱥ), precisely what in freudian theory is left in suspense of that escaped the phallic law in the said girls, due to the fact that this incidence comes from the field of the mother's desire, the feminine, therefore, which, in turn, takes into account what also escaped the phallic law. It is, in this sense, therefore, versed in the work that the Other is the field in which the subject gains consistency, since the subject is what a signifier represents to another signifier; however, jouissance being that which points to something that is of the order of an event of the body that is neither founded nor guaranteed in the relationship with the Other, the mode of jouissance in the feminine position is shown to be crossed by the symbolic, but there is something else in this enjoyment mode. The phallic signifier appears; however, it does not contain what the feminine represents. That is why its logic is that of being not-all phallic and, in the face of phallic jouissance, the mode of operation of its jouissance, which will be unique to each of the women, also announces another logic, supplementary and from which it is only semi-true says because it doesn't close.